2015
DOI: 10.14393/bj-v31n4a2015-26247
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and aggressiveness variation among Sclerotinia sclerotiorum dry bean isolates from Brazil fields

Abstract: Sclerotinia sclerotiorum, infection of bean fields, has increased in Brazil. Fungicides application is the control strategy used due to lack of cultivars with complete disease resistance. To guide the use of isolates in resistance screening 25 S. sclerotiorum isolates from Brazilian dry bean fields were characterized using microsatellite markers, mycelial compatibility groups (MCGs) and aggressiveness. Microsatellite primer pairs were used to identify polymorphisms among the S. sclerotiorum isolates and MCGs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
(25 reference statements)
1
9
0
3
Order By: Relevance
“…The greater aggressiveness of strain ScC was evident in the growth chamber, in comparison with strain ScS, even though this had been described as highly aggressive to soybeans (GARCIA; JULIATTI, 2012). Variability in S. sclerotiorum aggressiveness, reported in common beans, sunflower and soybeans (PRICE;CALHOUN, 1975;IRANI et al, 2011;ZANCAN et al, 2015), is commonly observed among strains isolated from different hosts or from distant geographical regions (KULL et al, 2004;DAVAR et al, 2011) due to variation in effector production (CASTRO et al, 2016). Such variability is relevant since, in breeding programs, the use of more aggressive strains is recommended in order to identify greater resistance levels in the germplasm collection (ZANCAN et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The greater aggressiveness of strain ScC was evident in the growth chamber, in comparison with strain ScS, even though this had been described as highly aggressive to soybeans (GARCIA; JULIATTI, 2012). Variability in S. sclerotiorum aggressiveness, reported in common beans, sunflower and soybeans (PRICE;CALHOUN, 1975;IRANI et al, 2011;ZANCAN et al, 2015), is commonly observed among strains isolated from different hosts or from distant geographical regions (KULL et al, 2004;DAVAR et al, 2011) due to variation in effector production (CASTRO et al, 2016). Such variability is relevant since, in breeding programs, the use of more aggressive strains is recommended in order to identify greater resistance levels in the germplasm collection (ZANCAN et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Variability in S. sclerotiorum aggressiveness, reported in common beans, sunflower and soybeans (PRICE;CALHOUN, 1975;IRANI et al, 2011;ZANCAN et al, 2015), is commonly observed among strains isolated from different hosts or from distant geographical regions (KULL et al, 2004;DAVAR et al, 2011) due to variation in effector production (CASTRO et al, 2016). Such variability is relevant since, in breeding programs, the use of more aggressive strains is recommended in order to identify greater resistance levels in the germplasm collection (ZANCAN et al, 2015). The result obtained in this study suggests a possible physiological specialization of S. sclerotiorum to its host, previously suggested (DAVAR et al, 2011) but still awaiting for omics studies about the interaction Sclerotinia-cotton to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that soybean genotypes should be selected for resistance using appropriately representative isolates. In Brazil, the importance of characterizing S. sclerotiorum isolate diversity has been investigated for dry bean resistance evaluations; however, little or no regional variation in aggressiveness was found and/or no interaction between isolate diversity and cultivars was observed (Koga et al 2014;Lehner et al 2016a, b;Zancan et al 2015). As such, resistance evaluations, should account for the regional variation within a pathogen population to ensure the development and release of a durable SSR-resistant varieties.…”
Section: Sclerotinia Sclerotiorum Population Structurementioning
confidence: 99%
“…In this study, the genotypic diversity varied from 0.64 to 0.71, which led the authors to speculate on the occurrence of outcrossing, but no specific analyses were performed to test this hypothesis. Recently, three papers addressing variability of S. sclerotiorum from dry bean fields in Brazil were published (Abreu and Souza 2015;Lehner et al 2015;Zancan et al 2015). All studies used SSR markers and MCGs to estimate the variability, but the conclusions were different.…”
Section: Sclerotinia Sclerotiorum Populations From Tropical Climate Smentioning
confidence: 99%